2019
DOI: 10.1002/cae.22177
|View full text |Cite
|
Sign up to set email alerts
|

Pencil Code improves learners' computational thinking and computer learning attitude

Abstract: In the current implementation of K‐12 education, computational thinking is considered an important part of developing students' key abilities. Many studies have shown that computational thinking can be improved by programming, for example, using Scratch, App Inventor, and Python. However, different programming tools have different forms of programming that affect the development of learners' computational thinking. This study aimed to test the effects of different programming tools with the same teaching conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 31 publications
0
33
0
2
Order By: Relevance
“…However, the most direct and effective means to train the students' CT is through programming [6,18]. Many research have proved that programming, such as using Python and App Inventor, can enhance CT [9]. Purdue University uses the Python language and Python libraries to teach CT through basic programming concepts, data practices, simulation practices, and visualization practices [28].…”
Section: Ct and Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the most direct and effective means to train the students' CT is through programming [6,18]. Many research have proved that programming, such as using Python and App Inventor, can enhance CT [9]. Purdue University uses the Python language and Python libraries to teach CT through basic programming concepts, data practices, simulation practices, and visualization practices [28].…”
Section: Ct and Programmingmentioning
confidence: 99%
“…Although there are many empirical analytics in the field of CT, no uniform evaluation standard has been reached until now [9]. Many researchers use the CTS scale developed by Korkmaz et al [16], which was considered as general CT evaluation method.…”
Section: Test Tools For Computational Concepts and Practicesmentioning
confidence: 99%
“…The mastery of programming language can also be enhanced using interactive and visual-looking programming software as shown in [9][10][11][12][13][14][15]. In a work by Erol and Kurt [9], students were divided into two groups, where, one group used Scratch's visual software and another group adopted the flowchart method, to learn the basic concepts of programming.…”
Section: Introductionmentioning
confidence: 99%
“…Another work by [11] analysed the effectiveness of interactive programming software that enables real-time feedback given to students when writing programmes. Other interactive tools like Pencil Code collaborative software [12], Resource Flow Diagram (RFD) [13], Alice microworld [14], and virtual reality [15] were also used to promote intuitive learning. The use of the interactive feedback system demonstrates an improvement in overall student achievement.…”
Section: Introductionmentioning
confidence: 99%
“…A learner modeling was presented, which can provide an open‐ended learning environment to support CT and synergistic learning of science for middle‐school students [2]. The effects of different programming tools for a benchmark problem on learners' CT and learning attitudes were investigated, with K‐12 students, and it was found that the Pencil‐Code programming environment was more conducive to improving students' CT skills and learning interest [11].…”
Section: Introductionmentioning
confidence: 99%